Diagnostic Assessment for Students who Enroll in Pedagogical Programs in Chilean State Universities: Social Representations about Teaching Professional Performance - Pavié-Nova, Alex (2020)
This descriptive and interpretative study accounts for results of representations regarding teaching profession which students of initial teaching training report in seven state chilean Higher Education institutions. This study arises from the updating of the national education quality assurance system in which the obligation to apply a diagnostic test is established. For such a purpose, the study population was composed by 1836 students from 2019 cohort of pedagogical programs from this national universities. A Likert - like scale instrument was applied. Numerical descriptive and inferential methods were applied to analyze the information. Generally concluding, common representations are revealed a professional performance regardless of the sex; it suggests that the evaluated subjects shape a clearly modeled professional identity before starting their Initial Teaching Training.